Net audiences: a comparison of the Sainsbury Normal Method and the Sainsbury Weighted Method. Issue 15 (12th October 2020) - Anesbury, Zachary William; Driesener, Carl Barrie; Page, Bill; Bellman, Steven; Sharp, Byron
ABSTRACT: For almost nine decades, advertisers have relied on the Sainsbury Normal Method (SNM) to estimate net-reach where single-source data are either too expensive or unavailable. To the best of the authors' knowledge, no SNM validation studies have included catalogues, smartphone applications, websites, social media, or cinema. While few studies have applied the SNM across media, no study has addressed the limitation of the SNM, that is, the implied assumption of audience homogeneity. Given that audiences do differ by age within any medium, and across media, there is a need to incorporate audience heterogeneity into the method. The authors introduce the Sainsbury Weighted Method (SWM) which provides more accurate within medium net-reach estimations in 82% of the 9, 680 cases analysed, with an average accuracy improvement for within medium net-reach estimations of 0.6 percentage points (or 13%). For across media net-reach, the SWM estimations are more accurate in 77% of the 968 cases analysed, improving the average accuracy by 0.5 percentage points (or 49%).